THE INFLUENCE OF THE BOARD OF DIRECTORS, RISK MANAGEMENT COMMITTEE, OWNERSHIP CONCENTRATION AND PROFITABILITY ON ENTERPRISE RISK MANAGEMENT - Wahyu Setiyowati, Supami; Diah, Diah Kusumaningrum; Sari, Ati Retna (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The aim of this research is to analyze the influence of the Board of Directors, Risk Management Committee, Ownership Concentration and Profitability on Enterprise Risk Management. The population used in this research is retail companies listed on the Indonesia Stock Exchange in 2016-2021. In that year, retail companies experienced fluctuations which caused a crisis in the Indonesian economy. This research used a purpove sampling technique so that 108 samples were obtained. Data analysis used the Statistical Program for Social Science (SPSS) version 25 application using research methods, namely quantitative methods.. The research results showed that the Board of Directors had a negative and significant effect on the Enterprise Risk Management variable. The Risk Management Committee has a positive and significant effect on the Enterprise Risk Management variable. Ownership Concentration has a positive and significant effect on the Enterprise Risk Management variable and Profitability has a positive and significant effect on the Enterprise Risk Management variable. The Board of Directors, Risk Management Committee, Ownership concentration and Profitability have a simultaneous influence on Enterprise Risk Management.